Retire inspired : it's not an age, it's a financial number - Hogan, Chris E. (Chris Elizabeth), 1964- (Ramsey Press, 2016)
When you hear the word retirement, you probably don't imagine yourself scrambling to pay your bills in your golden years. But for too many Americans, that's the fate that awaits unless they take steps now to plan for the future. Whether you're twenty-five and starting your first job or fifty-five and watching the career clock start to wind down, today is the day to get serious about your retirement. In Retire Inspired, Chris Hogan teaches that retirement isn't an age; it's a financial number--an amount you need to live the life in retirement that you've always dreamed of. With clear investing concepts and strategies, Chris will educate and empower you to make your own investing decisions, set reasonable expectations for your spouse and family, and build a dream team of experts to get you there. You don't have to retire broke, stressed, and working long after you want to. You can retire inspired!